Assessing the effectiveness of empowerment on service quality: A multi-level study of Chinese tourism firms. (August 2017) - Lin, Meizhen; Wu, Xiaoyi; Ling, Qian
Abstract: This study tests relationships among three levels of empowerment—organizational, departmental, and individual—and simultaneously their cascading effects on frontline employees' service quality. Drawing on data from 1566 employee-supervisor pairs from 123 departments in 53 Chinese hospitality and tourism enterprises, results reveal a cascading mechanism across three levels of empowerment. Organizational empowerment climate influences employees' psychological empowerment through department psychological empowerment, and department psychological empowerment influences employees' service quality through individual psychological empowerment. Cross-level moderation analysis suggests that only within a high degree of organizational empowerment climate and service behavior-based evaluation does employees' psychological empowerment have positive effects on service quality. In response to the debate on the merits of empowerment programs in organizations, this study supports the usefulness of a cascading, contingency model of empowerment, and demonstrates full delineation of how and when empowerment across three levels influence frontline employees' service quality. Highlights: A cascading effect of organizational-, departmental-, and individual-level empowerment to service quality persists. Organizational and departmental empowerment influence employees through distinct intervention mechanism. The effectiveness of employees' psychological empowerment depends on organizational context.